Diabetic retinopathy: Involved cells, biomarkers, and treatments - Ren, Jiahui; Zhang, Shuxia; Pan, Yunfeng; Jin, Meiqi; Li, Jiaxin; Luo, Yun; Sun, Xiaobo; Li, Guang (Frontiers in Pharmacology, 2022)
Diabetic retinopathy (DR) is the leading cause of vision loss and blindness worldwide. DR is caused by retinal neurovascular unit dysfunction, and its cellular pathology of DR involves at least nine kinds of retinal cells, including photoreceptors, horizontal and bipolar cells, amacrine cells, retinal ganglion cells, glial cells (Müller cells, astrocytes, and microglia), endothelial cells, pericytes, and retinal pigment epithelial cells. Its complicated mechanism has not yet been clarified clearly. In recent years, drug treatment for DR gradually grows up. The research on potential drug targets is based on clear pathogenesis and effective biomarkers. Therefore, we reviewed the recent literature on the cellular pathology, the diagnostic and prognostic biomarkers in terms of blood, protein, and the clinical and preclinical drug therapy (including western medicine and traditional Chinese medicine) of DR. This review maybe provided provide a theoretical basis for further research on DR.